2010
DOI: 10.1016/j.jacc.2010.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Origins of the Postural Orthostatic Tachycardia Syndrome

Abstract: Objectives To test the hypothesis that a small heart coupled with reduced blood volume contributes to the Postural Tachycardia Syndrome (POTS), while exercise training improves this syndrome. Background Patients with POTS have marked increases in heart rate during orthostasis. However, the underlying mechanisms are unknown and the effective therapy is uncertain. Methods Twenty-seven POTS patients underwent autonomic function tests, cardiac MRI, and blood volume measurements. Twenty-five of them participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
299
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(321 citation statements)
references
References 55 publications
13
299
0
9
Order By: Relevance
“…Decreased upright CO in POTS has been reported by our group and by others,27, 30, 31 and is associated with increased SVR,27, 31 consistent with sustained BP and marked reduction in upright stroke volume 32. However, a subset of POTS may have increased CO during exercise 33.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Decreased upright CO in POTS has been reported by our group and by others,27, 30, 31 and is associated with increased SVR,27, 31 consistent with sustained BP and marked reduction in upright stroke volume 32. However, a subset of POTS may have increased CO during exercise 33.…”
Section: Discussionsupporting
confidence: 64%
“…Supine CBV is reduced in some patients with POTS 31, 34, 35, 36. This is striking in those patients with evidence for increased supine sympathoexcitation 37.…”
Section: Discussionmentioning
confidence: 95%
“…4,5,25 In addition, reduced cerebral perfusion induced by excessive lowerbody venous pooling with delayed orthostatic hypotension has been suggested to be involved in the orthostatic component of fatigue in CFS patients. 26 Recently, by using a cardiac magnetic resonance imaging technique, Fu et al 13 assessed precisely the heart size and mass in patients with POTS and found that cardiac size and mass and blood volume were much smaller in the patients than in healthy sedentary controls. The marked orthostatic tachycardia in these patients seemed to be a physiologic compensatory response to a smaller stroke volume, and exercise training improved this syndrome in most patients.…”
Section: Discussionmentioning
confidence: 99%
“…The marked orthostatic tachycardia in these patients seemed to be a physiologic compensatory response to a smaller stroke volume, and exercise training improved this syndrome in most patients. 13 In their assessment of both sympathetic baroreflex sensitivity and cardiovagal baroreflex sensitivity, the function of the autonomic nervous system was intact in the patients, 13 although other researchers have postulated autonomic nervous dysfunction with exaggerated sympathetic nervous activation over compensatory levels while standing as a major mechanism behind the symptoms. 4,5,20,24,27 Elucidation of the pathophysiology of CFS and OI may lead to better therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation